The noonday friends eaudiobook - Stolz, Mary (Recorded Books Inc., 2019)
"You never can do anything except on weekends," Simone complained. "How can people be friends only on weekends?" Stiffening, Franny said, "If you don't want to be friends, Simone, then all right." Threatened, as she so often was, with tears, Franny, as she usually did, fought them back. "See if I care," she said airily. Franny does care-a lot. But what can she do? Her mother works long hours at the laundromat, and her father can't seem to hold down a regular job. And who is going to clean the house and look after 4-year-old Marshall? It all falls on Franny's shoulders. But Franny will suffer any indignity-even her shabby clothes and not having enough lunch money-if her best friend Simone is on her side. But lately, Simone keeps taking about dopey rich Lila, and all the free time she has to play. How can Franny and Simone be friends if they never see each other?